Análisis Financiero a la empresa comercial CALVA Y CALVA CIA. LTDA. de la ciudad de Loja. Periodos 2015 - 2016 - Martínez Vega, Tania Elizabeth (2018)
The thesis work called "FINANCIAL ANALYSIS TO THE COMMERCIAL COMPANY" CALVA Y CALVA CIA. LTDA "OF THE CITY OF LOJA. PERIODS 2015 - 2016 '' was executed in compliance with the previous requirement to choose the Bachelor's and Bachelor's Degree in Accounting and Auditing, Public Accountant-Auditor. The specific objective one is to perform the vertical and horizontal analysis, in order to know the participation of the different items that intervened in each of the financial statements and determine increases or variations of the different accounts that make up the financial statements. The specific objective two is to apply the Financial Indicators, which will allow to verify the financial and economic situation of the Calva y Calva Cia. Ltda Company; Representing greater attention from the shareholders are the following: it is the Current Reason, which consists of $ 1.13 for 2015 and for the year 2016 of $ 1.20, showing that the company does not have enough liquidity to cancel your short-term obligations. The Average Collection Period, revealing that in 2015 the portfolio was recovered at 115 days and for the year 2016 in 101 days demonstrating that the company does not have an efficient commercial and portfolio management for the early recovery of its loans granted by the sales made. The Level of Indebtedness, which reflects the company for the year 2015 has 100.87% and for the year 2016 of 99.32% demonstrating that the 5 commercial company is over indebted passing into the hands of the creditors, as it passes the be required which is 50%. In addition, the Performance on Equity indicator was applied, which indicates the percentage obtained in relation to the total investment made by the shareholders, reflecting that in 2015 it obtained 2.80% and for the year 2016 of 2.07%, meaning that for each dollar invested, a yield of 0.028 cents and 0.0207 cents were obtained, all these indicators were graphically represented and interpreted, they were developed according to the need and operative activity carried out by the company. The third specific objective is to make a report of the entire financial analysis process that will be socialized before the partners of the company and can take the necessary corrective measures to improve it. The methodology used for the present thesis work is the application of the vertical and horizontal method as well as the financial indicators that allowed verifying how each of the accounts that make up the financial statements are acting. The most relevant conclusion is that the purchase and sale policies of the limited company are not adequate since it is recovering its money after 115 days and 101 days for the years 2015 and 2016 respectively; not having a liquidity to be able to face the operation of the company.